Political equality and quality of government - Roberto Ezcurra; Izaskun Zuazu (Kyklos, 2022)
This paper examines the relationship between political equality and quality of government. Our hypothesis is that political equality fosters access to inclusive education and ultimately promotes good governance. We empirically test this hypothesis using data for 145 countries with different levels of economic development. In order to overcome potential endogeneity problems, our identification strategy exploits the variation in political equality in geographically neighbouring countries by means of spatial econometric techniques. The results reveal a positive and statistically significant effect of political equality on the quality of government. This implies that countries where political power is more evenly distributed tend on average to have higher levels of institutional quality. In fact, this result is not affected by the inclusion in the analysis of a substantial number of controls that may be correlated with both political equality and quality of government, including the extent of democracy and the degree of economic inequality. In fact, the observed link between political equality and governance remains robust to alternative measures of quality of government, estimation techniques, and other sensitivity checks. Our estimates also show that education acts as a transmission channel linking political equality and quality of government.
Keywords: 300